CitE Enzymes Are Essential for Mycobacterium tuberculosis to Establish Infection in Macrophages and Guinea Pigs - Arora, Garima; Chaudhary, Deepika; Kidwai, Saqib; Sharma, Deepak; Singh, Ramandeep (Frontiers in Cellular and Infection Microbiology, 2018)
Bacterial citrate lyase activity has been demonstrated in various eukaryotes, bacteria and archaea, underscoring their importance in energy metabolism of the cell. While the bacterial citrate lyase comprises of three different subunits, M. tuberculosis genome lacks CitD and CitF subunits of citrate lyase complex but encodes for 2 homologs of CitE subunits, Rv2498c and Rv3075c. Using temperature sensitive mycobacteriophages, we were able to generate both single and double citE mutant strains of M. tuberculosis. The survival experiments revealed increased susceptibility of the double mutant strain to oxidative stress in comparison to the parental strain. Also, simultaneous deletion of both citE1 and citE2 in M. tuberculosis genome also resulted in impairment of intracellular replication in macrophages. The double mutant strain displayed reduced growth in lungs and spleens of guinea pigs. This is the first study demonstrating that M. tuberculosis critically requires CitE subunits of citrate lyase for pathogenesis. Taken together, these findings position these enzymes as potential targets for development of anti-tubercular small molecules.